A Blueprint for the Synthesis and Characterization of Thiolated Graphene - Rabchinskii, Maxim K.; Sysoev, Victor V.; Ryzhkov, Sergei A.; Eliseyev, Ilya A.; Stolyarova, Dina Yu; Antonov, Grigorii A.; Struchkov, Nikolai S.; Brzhezinskaya, Maria; Kirilenko, Demid A.; Pavlov, Sergei I.; Palenov, Mihail E.; Mishin, Maxim V.; et al. (Nanomaterials (Basel, Switzerland), 2021)
Graphene derivatization to either engineer its physical and chemical properties or overcome the problem of the facile synthesis of nanographenes is a subject of significant attention in the nanomaterials research community. In this paper, we propose a facile and scalable method for the synthesis of thiolated graphene via a two-step liquid-phase treatment of graphene oxide (GO). Employing the core-level methods, the introduction of up to 5.1 at.% of thiols is indicated with the simultaneous rise of the C/O ratio to 16.8. The crumpling of the graphene layer upon thiolation without its perforation is pointed out by microscopic and Raman studies. The conductance of thiolated graphene is revealed to be driven by the Mott hopping mechanism with the sheet resistance values of 2.15 kΩ/sq and dependable on the environment. The preliminary results on the chemiresistive effect of these films upon exposure to ethanol vapors in the mix with dry and humid air are shown. Finally, the work function value and valence band structure of thiolated graphene are analyzed. Taken together, the developed method and findings of the morphology and physics of the thiolated graphene guide the further application of this derivative in energy storage, sensing devices, and smart materials.